Current Perspectives on Opisthorchiasis Control and Cholangiocarcinoma Detection in Southeast Asia - Khuntikeo, Narong; Titapun, Attapol; Loilome, Watcharin; Yongvanit, Puangrat; Thinkhamrop, Bandit; Chamadol, Nittaya; Boonmars, Thidarat; Nethanomsak, Teerachai; Andrews, Ross H.; Petney, Trevor N.; Sithithaworn, Paiboon (Frontiers in Medicine, 2018)
Similar to cholangiocarcinoma (CCA) in the western world, opisthorchiasis-associated CCA in Southeast Asia is an aggressive cancer with high mortality rates. It is known to cause a significant health burden in the endemic area of opisthorchiasis in Thailand and possibly in Southeast Asian. To reduce this health burden, a comprehensive prevention and control program for opisthorchiasis, as well as CCA, are required. In this review, our aim is to provide a brief update of the current situation regarding opisthorchiasis and the pathogenesis and health burden of CCA in Southeast Asia, and to discuss a comprehensive approach to tackling these issues being implemented in Thailand under the “Cholangiocarcinoma Screening and Care Program” (CASCAP). This comprehensive program consists of a primary and secondary to tertiary prevention and patient care program. The primary prevention component involves opisthorchiasis screening using a new and sensitive urine assay. The secondary prevention component involves screening for CCA and periductal fibrosis, with suspected CCA patients following the protocol for confirmation and appropriate treatment. Due to the eco-epidemiology of opisthorchiasis-induced cholangiocarcinoma, the anticipated impacts and outcomes of the program include short, medium and the long-term goals for the reduction of CCA incidence. To achieve such long-term and sustainable impacts, concerted efforts to raise social awareness and participating action by civilians, non-government organizations and government agencies are necessary. The strategic plans developed for this program can be expanded for use in other endemic areas as well as being a model for use in other chronic diseases.